No differences in hemostatic and endothelial activations between haploidentical and matched-donor hematopoietic stem cell transplantation in thalassemia disease - Surapong Lertthammakiat; Peerasit Sitthirat; Usanarat Anurathapan; Duantida Songdej; Samart Pakakasama; Ampaiwan Chuansumrit; Nattaphat Putawornsub; Sawitt Sirasittikarn; Sataporn Wantanawijarn; Praguywan Kadegasem; Suradej Hongeng; Nongnuch Sirachainan (Thrombosis Journal, 2020)
Abstract Hemostatic changes and endothelial activations have been recognized in β-thalassemic patients after matched-donor hematopoietic stem cell transplantation (HSCT) but there are limited studies for haploidentical HSCT. This report demonstrates that the levels of hemostatic and endothelial markers, including thrombin antithrombin complex, prothrombin fragment, D-dimer, von Willebrand factor antigen and thrombomodulin levels, were not significantly different between haploidentical and matched-donor HSCT patients.